2011
DOI: 10.1177/0040517511426608
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of capsaicin-coated wool fabric

Abstract: Fabrics made from natural fibers, such as wool and cotton, are susceptible to attacks from micro-organisms, which may damage the fabrics and harm the human body. Antimicrobial finishing of natural textile products may involve harmful and non-environmentally friendly chemicals. In this study, a natural antibacterial agent, capsaicin, was coated on the surface of wool fabrics by a sol-gel process. The antibacterial properties of coated fabrics were evaluated against test bacteria Escherichia coli according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Antifungal potential has been attributed to capsaicin, mainly against Penicillium expansum, Trametes versicolor, and Gloeophyllum trabeum. On the other hand, it can be used to treat some viral infections like herpes simplex virus (HSV) disease in guinea pigs, HSV infections, and genital herpes (Akhtar et al, 2017;Liu, Lin, Peng, & Wang, 2012;Marini, Magi, Mingoia, Pugnaloni, & Facinelli, 2015). Likewise, Nazzaro et al (2009) suggested that pepper products could be used to develop new antimicrobial agents for food preservation, to control foodborne pathogens in foods and/or product spoilage avoiding the use of synthetic preservatives.…”
Section: Antimicrobial Antifungal and Antiviral Activitymentioning
confidence: 99%
“…Antifungal potential has been attributed to capsaicin, mainly against Penicillium expansum, Trametes versicolor, and Gloeophyllum trabeum. On the other hand, it can be used to treat some viral infections like herpes simplex virus (HSV) disease in guinea pigs, HSV infections, and genital herpes (Akhtar et al, 2017;Liu, Lin, Peng, & Wang, 2012;Marini, Magi, Mingoia, Pugnaloni, & Facinelli, 2015). Likewise, Nazzaro et al (2009) suggested that pepper products could be used to develop new antimicrobial agents for food preservation, to control foodborne pathogens in foods and/or product spoilage avoiding the use of synthetic preservatives.…”
Section: Antimicrobial Antifungal and Antiviral Activitymentioning
confidence: 99%
“…The antimicrobial activity was assessed referring to the standard shake flask method (ASTM-E2149-01) [43][44][45][46][47], which could determine the antimicrobial activity. This method provides quantitative data for measuring the reduction rate in a number of colonies formed, converted to the average colony forming units per milliliter of buffer solution in the flask (CFU/mL).…”
Section: Antibacterial Testmentioning
confidence: 99%
“…Capsaicin has been widely used in pharmaceutical and medical applications due to its remarkable properties, such as boosting metabolism to increase amount of heat in body and burn more calories [7], reducing blood pressure [8], helping dilation of blood vessel [9], and improving blood circulation [10]. Capsaicin also has antioxidative [11], antibacterial [12] and anticarcinogenic [13] properties.…”
Section: Introductionmentioning
confidence: 99%